NOV (nephroblastoma overexpressed) and the CCN family of genes: structural and functional issues. Issue 2 (1st April 2001) - Perbal, B
Abstract : The CCN family of genes presently consists of six distinct members encoding proteins that participate in fundamental biological processes such as cell proliferation, attachment, migration, differentiation, wound healing, angiogenesis, and several pathologies including fibrosis and tumorigenesis. Whereas CYR61 and CTGF were reported to act as positive regulators of cell growth, NOV (nephroblastoma overexpressed) provided the first example of a CCN protein with negative regulatory properties and the first example of aberrant expression being associated with tumour development. The subsequent discovery of the ELM1, rCOP1, and WISP proteins has broadened the variety of functions attributed to the CCN proteins and has extended previous observations to other biological systems. This review discusses fundamental questions regarding the regulation of CCN gene expression in normal and pathological conditions, and the structural basis for their specific biological activity. After discussing the role of nov and other CCN proteins in the development of a variety of different tissues such as kidney, nervous system, muscle, cartilage, and bone, the altered expression of the CCN proteins in various pathologies is discussed, with an emphasis on the altered expression of nov in many different tumour types such as Wilms's tumour, renal cell carcinomas, prostate carcinomas, osteosarcomas, chondrosarcomas, adrenocortical carcinomas, and neuroblastomas. The possible use of nov as a tool for molecular medicine is also discussed. The variety of biological functions attributed to the CCN proteins has led to the proposal of a model in which physical interactions between the amino and carboxy portions of the CCN proteins modulate their biological activity and ensure a proper balance of positive and negative signals through interactions with other partners. In this model, disruption of the secondary structure of the CCN proteins induced by deletions of either terminus is expected to confer on the truncated polypeptide constitutive positive or negative activities.